Apoio à decisão multicritério para o consumidor no mercado de plano privado de assistência à saúde - Cerceau, Renato (2018)
This work develops an evaluation model that allows the accomplishment of comparisons about products (or health plans) offered by Private Health Insurance and Plans Company (or operator). In addition, it provides a monitoring tool that allows better follow-up to help the decision process, making the individual more active. A computational system was developed to support the decision-making process in three phases: ’assisted’, ’supervised’ and ’self-driven’. The modeling used ELECTRE multicriteria methodology providing experimental results that corroborate the predicted results analytically. As a final product, there is greater availability of information to the citizen to support the decision-making process, receiving the recommendations through the tool developed to perform the comparative analyzes.